Recent advancement in the method of transdermal drug delivery system: A review - Halder, Sudip; Chakraborty, Prodipta; Pradhan, Darshan; Bagchi, Arnab (Journal of Applied Pharmaceutical Research, 2021)
A transdermal patch is a medicated adhesive patch that is applied to the skin and used to deliver a particular amount of medication into the bloodstream through the skin. It aids in the recovery of an injured bodily part. The transdermal drug delivery system (TDDS) provides an alternative safe means of drug delivery to previous intrusive techniques. In the past, topically applied lotions and ointments were the most commonly utilised systems for dermatological issues. The fact that some of these formulations cause systemic side effects indicates that they are absorbed through the skin. All topically applied medication formulations intended to transport the active ingredient into the general circulation are included in the transdermal delivery system. To overcome the skin's formidable barrier to topical medication administration, several substances have been utilised. Because of their unique qualities, such as improved bioavailability, regulated pharmaceutical release, and improved patient compliance, TDDS have recently gained increased attention. The current review focuses on the various advancements in transdermal drug delivery, as well as the various available methods for preparing transdermal patches, characterization and assessment tools for transdermal patch preparation, patents, transdermal compound clinical trials, and drug approved and future applications of transdermal drug delivery systems. As a result, in recent years, the Transdermal Drug Delivery System has received a lot of attention.